Research on the Symbiotic Development of University Dance Education and Intangible Cultural Heritage: Focusing on Regional Dances of Shandong - Wang, Lin; Raj, Sumathi Maniam; Saw, Eu Gene (International Journal of Humanities and Social Science, 2026)
This review explores the symbiotic development of university dance education and intangible cultural heritage (ICH), with a particular focus on the regional dances of Shandong, China. It examines how integrating traditional dance forms—such as Yangko, Folk Lantern Dance, Drum Dance, and Plum Blossom Dance—into higher education curricula can simultaneously enhance students’ technical skills, creativity, aesthetic literacy, and cultural identity. The paper synthesizes theoretical frameworks, empirical studies, and practical models to highlight mutually reinforcing relationships between pedagogical practices and heritage preservation. Key strategies, including curricular integration, workshops, community collaboration, and research-based approaches, are discussed alongside challenges related to authenticity, resource constraints, and evaluative measures. Findings indicate that symbiotic programs foster not only artistic competence but also cultural awareness, social engagement, and sustainable transmission of regional dance traditions. The review also identifies gaps in current research, emphasizing the need for longitudinal studies, standardized assessment frameworks, and interdisciplinary approaches to maximize educational and heritage outcomes. Overall, this study underscores the potential of university dance programs to serve as active agents in the preservation, innovation, and dissemination of ICH.